2021
DOI: 10.3389/pore.2021.1609743
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Retraction Clefts in Chinese Invasive Breast Cancer Patients

Abstract: Some studies reported the correlation between retraction clefts (RCs) and the clinicopathological features as well as prognosis in invasive breast carcinoma. However, limited number of investigations have been done and controversial results were reported. Larger population studies around the world might help to provide more accurate and comprehensive information. Thus, we examined the correlation between the extent of RCs and the clinicopathological features as well as the prognosis in 541 invasive breast carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…The presence of retraction clefts: This phenomenon has been described in some tumor types and involves the presence of empty spaces around tumor nests[ 25 , 26 ]. Several studies have demonstrated that the presence of retraction clefts may be associated with a poor prognosis in patients with various malignant tumors[ 27 - 29 ] or more aggressive tumors[ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of retraction clefts: This phenomenon has been described in some tumor types and involves the presence of empty spaces around tumor nests[ 25 , 26 ]. Several studies have demonstrated that the presence of retraction clefts may be associated with a poor prognosis in patients with various malignant tumors[ 27 - 29 ] or more aggressive tumors[ 30 ].…”
Section: Resultsmentioning
confidence: 99%